2(m-3)=3m+3

Simple and best practice solution for 2(m-3)=3m+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(m-3)=3m+3 equation:



2(m-3)=3m+3
We move all terms to the left:
2(m-3)-(3m+3)=0
We multiply parentheses
2m-(3m+3)-6=0
We get rid of parentheses
2m-3m-3-6=0
We add all the numbers together, and all the variables
-1m-9=0
We move all terms containing m to the left, all other terms to the right
-m=9
m=9/-1
m=-9

See similar equations:

| 32=x+0.29x | | -16=-6x+4(x-7) | | 13-14y+y^2=0 | | (x-12)/6+14=9+6 | | 64w+56=56w | | 8x-0.5=6 | | 6x+8x+1/4=383/4 | | 5(-3x-2)-(x-3)=-4(4x+5)+13=666 | | 16-(-4y)=-28 | | 6x-5.45=-1.31 | | 8x-5.66=-3.18 | | 133(y+9)=12y+13 | | 0=6-2p | | (2x/2x+4)+(15/5x+10)=(24/6x+12) | | 0=4x^2+18x-252 | | -6=-2/9u | | n/6-4=-1 | | 10x-8=-12x-8 | | n/2-7=1 | | n/4+1=11 | | -b+4b=-8b-b | | x+11/12=3/8 | | 6x3+42x^2=0 | | -7=3(w+3)-7w | | 14y+44=100 | | 114=-6d+6 | | 114=6d+6 | | 20=3r-7 | | 7t=51 | | 3g=22 | | 3/9-x=1/12 | | -t^2+90t=1000 |

Equations solver categories